Qualitatively exploring the impact of a relationship-centered communication skills training program in improving patient perceptions of care - Marie C. Haverfield; Robert Victor; Brenda Flores; Jonathan Altamirano; Magali Fassiotto; Merisa Kline; Barbette Weimer-Elder (Elsevier, 2022)
Objective: To explore qualitative patient experience comments before and after a relationship-centered communication skills training to understand patient experience, program impact, and opportunities for improvement. Methods: Qualitative patient experience evaluation data was captured from January 2016 to December 2018 for 483 health care clinicians who participated in the skills training. A random sampling of available open-ended patient comments (N = 33,223) were selected pre-training (n = 668) and post-training (n = 566). Comments were coded for valence (negative/neutral/positive), generality versus specificity, and based on 12 communication behaviors reflective of training objectives. Results: No significant difference was found in the valence of comments, or generality versus specificity of comments before and after the training. A significant decrease was present in perceived clinician concern. "Confidence in care provider" was the communication skill most frequently identified in comments both pre- and post-training. Conclusion: Perceptions of interactions largely remained the same following training. Key relationship-centered communication skills require further attention in future training efforts. Measurements of patient satisfaction and engagement may not adequately represent patient experience. Innovation: This study identified areas for improvement in the training program and offers a model for utilizing patient experience qualitative data in understanding communication training impact.